World wide web : how to design and construct home pages - Bradley, Phil (Aslib LondonGB, 1995)
Provides the theory behind the creation of the Web, why it is so popular, and the kind of information one can locate on it. Guides one through the creation of a simple home page, and lists some of the resources available that would help in the creation of more complex home pages.